APPLICATION GIS IDENTIFY LAND AREA SUITABLE FOR RUBBER AND COFFEE TREES TO AGRICULTURE RESTRUCTURE GIA LAI PROVINCE - Thi Bich, Nguyen; Xuan Phuong, Hoang (Journal of Forestry Science and Technology, 2023)
Gia Lai has great potential for developing agricultural production, and it is home to a large crop industrial material area in Vietnam. It boasts nearly 100,000 hectares of coffee and nearly 90,000 hectares of rubber. The area has immense potential to develop its agricultural production due to its unique characteristics of soil and climate, which can support a rich diversity of plants and animal with high economic value. By creating areas for intensive agricultural production and concentrating on commodity products with a competitive advantage, Gia Lai can improve the efficiency of its agricultural restructuring. To achieve this goal, this research has utilized the Land Evaluation Method of the FAO method and GIS to identify suitable land areas for rubber and coffee trees to restructure agriculture in Gia Lai province. the results indicate that the land suitability for coffee trees is mainly moderately suitable (S2) with 86,163 hectares of land suitable for cultivation. Coffee trees are primarily grown in districts such as Chu Pah, Dak Doa, Chu Se and Ia Grai. On the other hand, the land suitability for rubber trees is mainly moderately suitable (S2) with 60,000 hectares of land suitable for cultivation. Rubber trees are primarily grown in districts such as Chu Pah, Dak Doa, Chu Se, Ia Grai and Chu Prong. These areas are characterized by the distribution of red basaltic soils, rainfall exceeding 2500 mm, and a favorable climate for the development of industrial plants.